2016
DOI: 10.1111/eth.12518
|View full text |Cite
|
Sign up to set email alerts
|

Free Amino Acids Mediate Association Preferences in Fish

Abstract: Chemical information is used in a variety of contexts including habitat recognition, foraging and predator avoidance, and a plethora of studies have shown that an individual's distinct chemical profile can mediate interactions with conspecifics. Interestingly, recent work has revealed that diet alone is sufficient to change the chemical profile of individuals, and with it, the way other individuals perceive and interact with them. Free amino acids are known to be utilised across species in a range of contexts,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 34 publications
(103 reference statements)
0
16
1
Order By: Relevance
“…It has been suggested that behavioural impairment towards chemical cues caused by freshwater acidification can either be mediated by the molecular change of the chemical cues themselves (Brown, Adrian, Lewis, & Tower, ; Leduc et al, ) or caused by a disruption of the fishes’ chemosensory receptor systems (Brown et al, ; Moore, ; Royce‐Malmgren & Watson, ; Tierney & Atema, ). Free amino acids have been postulated to underpin diet‐mediated interactions within shoaling fish (Atton et al, ; Kleinhappel, Burman, et al, ; Kleinhappel et al, ) and, as the isoelectric point of different free amino acids lies at different pH values (Lehninger, Nelson, & Cox, ), pH could change the charge of the amino acid which could then interfere with the amino acid receptor interaction (Royce‐Malmgren & Watson, ). An artificial change in pH has indeed been shown to change the behaviour, such as attraction or avoidance, of fish towards free amino acids (Royce‐Malmgren & Watson, ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been suggested that behavioural impairment towards chemical cues caused by freshwater acidification can either be mediated by the molecular change of the chemical cues themselves (Brown, Adrian, Lewis, & Tower, ; Leduc et al, ) or caused by a disruption of the fishes’ chemosensory receptor systems (Brown et al, ; Moore, ; Royce‐Malmgren & Watson, ; Tierney & Atema, ). Free amino acids have been postulated to underpin diet‐mediated interactions within shoaling fish (Atton et al, ; Kleinhappel, Burman, et al, ; Kleinhappel et al, ) and, as the isoelectric point of different free amino acids lies at different pH values (Lehninger, Nelson, & Cox, ), pH could change the charge of the amino acid which could then interfere with the amino acid receptor interaction (Royce‐Malmgren & Watson, ). An artificial change in pH has indeed been shown to change the behaviour, such as attraction or avoidance, of fish towards free amino acids (Royce‐Malmgren & Watson, ).…”
Section: Discussionmentioning
confidence: 99%
“…During data collection, each group consisted of two fish fed with the same diet and one fish fed on a different one, counterbalanced over diet conditions. Shoals were randomly assigned to one of two treatment groups: (a) the low pH condition in which fish were tested in water with a pH ranging between 6.2 and 6.4 (measured using a Benchtop digital pH meter) and (b) the high pH condition in which fish were tested in a pH ranging between 8.3 and 8.5, which was comparable to their normal housing water and the water used in previous experiments (pH range 8.2–8.4, unpublished data) (Kleinhappel, Burman, et al, ; Kleinhappel et al, ). Experiments were conducted in artificial freshwater, the preparation of which was varied in order to manipulate the water pH.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations